2007
DOI: 10.1152/ajpregu.00884.2006
|View full text |Cite
|
Sign up to set email alerts
|

Venous hemodynamic responses to acute temperature increase in the rainbow trout (Oncorhynchus mykiss)

Abstract: Many ectotherms regularly experience considerable short-term variations in environmental temperature, which affects their body temperature. Here we investigate the cardiovascular responses to a stepwise acute temperature increase from 10 to 13 and 16 degrees C in rainbow trout (Oncorhynchus mykiss). Cardiac output increased by 20 and 31% at 13 and 16 degrees C, respectively. This increase was entirely mediated by an increased heart rate (fH), whereas stroke volume (SV) decreased significantly by 20% at 16 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 54 publications
3
41
0
Order By: Relevance
“…The higher oxygen consumption demands in warm-acclimated fish require an increased workload from the cardiovascular system to support an elevated capacity to provide oxygen to the cells. A number of studies have demonstrated a strong relationship between changing metabolic rates and heart rates (Brodeur, 2001;Farrell, 2002;Gollock et al, 2006;Sandblom and Axelsson, 2007;Clark et al, 2008a;Steinhausen et al, 2008;Casselman et al, 2012). The current heart rate data show a similar relationship with metabolic rates and are discussed in detail below.…”
Section: Metabolic Rate During Recovery From An Acute Thermal Stressmentioning
confidence: 67%
See 1 more Smart Citation
“…The higher oxygen consumption demands in warm-acclimated fish require an increased workload from the cardiovascular system to support an elevated capacity to provide oxygen to the cells. A number of studies have demonstrated a strong relationship between changing metabolic rates and heart rates (Brodeur, 2001;Farrell, 2002;Gollock et al, 2006;Sandblom and Axelsson, 2007;Clark et al, 2008a;Steinhausen et al, 2008;Casselman et al, 2012). The current heart rate data show a similar relationship with metabolic rates and are discussed in detail below.…”
Section: Metabolic Rate During Recovery From An Acute Thermal Stressmentioning
confidence: 67%
“…To determine whether the changes in oxygen consumption were due to oxygen debt incurred by increased anaerobic metabolism during acute heat stress, we measured blood lactate concentration before and after the stress event (Brooks and Gaesser, 1980). Heart rate measurements were used to develop an index for cardiac performance, as most studies show that an increase in cardiac output in fish during an acute rise in temperature is primarily due to increased heart rates (Farrell, 2002;Gollock et al, 2006;Steinhausen et al, 2008;Sandblom and Axelsson, 2007;Clark et al, 2008a;Casselman et al, 2012). Therefore, we quantified several parameters of heart rate under resting conditions in response to acclimation and acute exposure to temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…Interpreting Ca O2 data during warming is more complex because of potential pH and temperature effects on the Hb-oxygen affinity curve, and because warming has variable effects on blood [Hb] (Taylor et al, 1997;Farrell, 1997;Sandblom and Axelsson, 2007). Even so, Ca O2 was maintained in resting sockeye salmon warmed to T crit as well as in exercising sockeye salmon warmed above T opt (Steinhausen et al, 2008).…”
Section: The Fry Curve For Aerobic Scopementioning
confidence: 99%
“…Warming increases cardiac output solely by increasing heart rate. This is true for both resting and exercising salmonids (Sandblom and Axelsson, 2007;Clark et al, 2008a;Steinhausen et al, 2008), presumably through a direct temperature effect on the cardiac pacemaker rate (Randall, 1970). However, because fish have a maximum heart rate (Farrell, 1991) and heart rate is already elevated by the exercise, the maximum heart rate must be reached at a temperature well below that for resting fish (Steinhausen et al, 2008).…”
Section: The Fry Curve For Aerobic Scopementioning
confidence: 99%
“…However, it is well known that acute exposure to high temperatures results in depression of cardiac output (Gollock et al, 2006;Sandblom and Axelsson, 2007;Steinhausen et al, 2008), possibly due to temperature-related changes in electrical excitability. Since stroke volume is fairly insensitive to temperature increases, modulation of cardiac output is achieved by temperatureinduced changes in f H .…”
Section: Introductionmentioning
confidence: 99%